Effect of tobacco smoking on outcomes of trabeculectomy - Acosta,Nadia Rios (2022)
ABSTRACT Purpose: To evaluate the effect of tobacco smoking on trabeculectomy outcomes. Methods: Charts of patients with glaucoma who underwent trabeculectomy performed by a single surgeon between 2007 and 2016 were retrospectively reviewed. Charts were screened for a documented history of smoking status before surgery. Demographic and clinical preoperative variables were recorded. Based on smoking history, subjects were divided into two groups: smokers and nonsmokers. Any bleb-related interventions (e.g., 5-flourouracil injections ± laser suture lysis) or bleb revision performed during the postoperative period were noted. Success was defined as an intraocular pressure >5 mmHg and <21 mm Hg without (complete success) or with (qualified success) the use of ocular hypotensive medications. Failure was identified as a violation of the criteria mentioned above. Results: A total of 98 eyes from 83 subjects were included. The mean age of the subjects was 70.7 ± 11.09 years, and 53% (44/83) were female. The most common diagnosis was primary open-angle glaucoma in 47 cases (47.9%). The smokers Group included 30 eyes from 30 subjects. When compared with nonsmokers, smokers had a significantly worse preoperative best-corrected visual acuity (p=0.038), greater central corneal thickness (p=0.047), and higher preoperative intraocular pressure (p=0.011). The success rate of trabeculectomy surgery at 1 year was 56.7% in the smokers Group compared with 79.4% in the Group nonsmokers (p=0.020). Smoking presented an odds ratio for failure of 2.95 (95% confidence interval, 1.6-7.84). Conclusion: Smokers demonstrated a significantly lower success rate 1 year after trabeculectomy compared with nonsmokers and a higher requirement for bleb-related interventions.